2004
DOI: 10.1152/ajpendo.00329.2003
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of type 2 diabeticdb/dbmice with a novel PPARγ agonist improves cardiac metabolism but not contractile function

Abstract: Treatment of type 2 diabetic db/db mice with a novel PPAR␥ agonist improves cardiac metabolism but not contractile function. Am J Physiol Endocrinol Metab 286: E449-E455, 2004. First published November 4, 2003 10.1152/ajpendo.00329.2003.-Hearts from insulin-resistant type 2 diabetic db/db mice exhibit features of a diabetic cardiomyopathy with altered metabolism of exogenous substrates and reduced contractile performance. Therefore, the effect of chronic oral administration of 2-(2-(4-phenoxy-2-propylphenoxy)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
77
2
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 53 publications
8
77
2
1
Order By: Relevance
“…A few studies used echocardiography to evaluate cardiac dysfunction in diabetic mouse models including both type 1 15,30) and type 2 diabetes. 14,31,32) In regarding to type 1 diabetes, our results are consistent with study of Shiomi et al 30) and inconsistent with the study of Nielsen et al 15) which revealed a slight increase in LVEDD and LVESD in diabetic mice 3 months after STZ treatment. These discrepancies may be due to the use of anesthesia, 10,33) the duration of diabetes 34) and, perhaps more importantly, the type of diabetic models.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…A few studies used echocardiography to evaluate cardiac dysfunction in diabetic mouse models including both type 1 15,30) and type 2 diabetes. 14,31,32) In regarding to type 1 diabetes, our results are consistent with study of Shiomi et al 30) and inconsistent with the study of Nielsen et al 15) which revealed a slight increase in LVEDD and LVESD in diabetic mice 3 months after STZ treatment. These discrepancies may be due to the use of anesthesia, 10,33) the duration of diabetes 34) and, perhaps more importantly, the type of diabetic models.…”
Section: Discussioncontrasting
confidence: 50%
“…These discrepancies may be due to the use of anesthesia, 10,33) the duration of diabetes 34) and, perhaps more importantly, the type of diabetic models. For instance, in the studies of Shiome et al 30) and the present study, tribromoethanol/amylene hydrate (Avertin) was used, and in the study of Nielsen et al 15) hypnorm/diazepam (1 : 1) was used, while in other studies, 14,32) no anesthesia was used. In addition, we examined a single-high-dose STZ-induced type 1 diabetic model, which is same as that in the study by Shiome et al, 30) whereas others used either type 2 diabetes (db/db mice or high-fat-induced diabetes) 14,31,32) or type-1 diabetes induced by multiplelow dose of STZ.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Using echocardiography, reduced fractional shortening and a reduction in the velocity of circumferential shortening have been demonstrated (Semeniuk et al, 2002;Carley et al, 2004;Pereira et al, 2006). Cardiac output, LV-developed pressure and cardiac power are all reduced in isolated, working db/db hearts, whereas LV end diastolic pressure is increased (Belke et al, 2000;Aasum et al, 2003;Carley et al, 2004;Hafstad et al, 2006;Hafstad et al, 2007). Similar contractile deficits are observed in Langendorff-perfused db/db hearts, in which ±dP/dt, peak systolic pressure, rate pressure product and developed pressure are all reduced Disease Models & Mechanisms DMM PERSPECTIVE .…”
Section: The Db/db Mousementioning
confidence: 99%
“…Because expression of Angptl4 is increased by PPAR␥ activation both in vitro and in vivo, a role of Angptl4 in mediating the biological activity of thiazolidinediones (TZDs) has been suggested (13). Notably, treatment with TZDs has been shown to be associated with increased incidence of cardiac hypertrophy and diminished cardiac fatty acid catabolism in preclinical species (16)(17)(18). However, the molecular events leading to this observation remain elusive.…”
mentioning
confidence: 99%